1978
DOI: 10.1302/0301-620x.60b1.342531
|View full text |Cite
|
Sign up to set email alerts
|

The clinical use of combined xenografts of bone and autologous red marrow. A preliminary report

Abstract: The beneficial effect upon osteogenesis of imprenating bone grafts with autologous red marrow is well documented. The experimental findings reported in a previous paper suggested that prepared xenograft bone might provide a good medium for osteogenesis by marrow cells. This paper is a preliminary report of the first clinical attempt to use xenografts of bone combined with autologous red marrow. Kiel bone, which was found the most suitable, was impregnated with marrow aspirated from the iliac crest and, apart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 0 publications
0
29
0
6
Order By: Relevance
“…Some experimental and clinical trials performed after this development have shown that impregnation of various types of bone graft with autologous red marrow has had beneficial effects on osteogenesis [10,11,16,[19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experimental and clinical trials performed after this development have shown that impregnation of various types of bone graft with autologous red marrow has had beneficial effects on osteogenesis [10,11,16,[19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in several clinical and experimental studies that treatment of bony defects and some other bone pathologies with a combination of autologous bone marrow and xenograft produced good results [10,16,[19][20][21][22] . In this study, no significant difference was found with respect to radiological findings between the groups during the first 15 days of the grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous bone marrow aspirated from the iliac crest had a beneficial effect upon osteogenesis when implanted with xenograft bone graft material (Kiel bone) [16], and the addition of BMA to autograft iliac crest bone graft facilitated greater bone formation and successful fusion in a rabbit posterolateral spine fusion model [5]. Furthermore, it was found that xenograft bone and other bone substitutes could be rendered osteogenic by combining them with fresh BMA [20].…”
Section: Bone Marrow Aspirate and Bone Compositesmentioning
confidence: 99%
“…This potential is employed in tissue repair and regeneration, treatment of bone defects, cysts [3,4,5,9] and even during distraction osteogenesis [17]. The beneficial effect of bone marrow can be enhanced by creating composite grafts with demineralised bone matrix, different carriers or stimulatory factors [11,13,14,18]. However, the combination of homologous compressed cancellous bone and bone marrow has not been previously evaluated as a treatment option for large bone defects.…”
Section: Introductionmentioning
confidence: 99%